Analisis Pengaruh Kinerja Keuangan Saat Pandemi Covid 19 Terhadap Harga Saham Pada Perusahaan Industri Manufaktur Sektor Aneka Industri di Subsektor Otomotif dan Komponen (Automotive and Components) Yang Terdaftar di BEI (Tahun 2019-2021) - Ryo Aditya Pratama; Nanu Hasanuh (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this research was to determine the effect of financial performance as measured by EPS, PER, DER and ROA on stock prices in automotive and component companies on the Indonesia Stock Exchange. Methods Sampling used the purposive sampling method from 14 companies listed on the Indonesia Stock Exchange in 2019-2021, only 12 companies were used in the research sample with a total of 33 data. The research method used is quantitative, using financial ratios and the type of causal/correlation research. The method of data analysis using multiple linear regression analysis and previously checked with the classical assumption test to show the feasibility of the data using SPSS 25 software. The partial test results show that the four variables used by the research model that have a significant influence on stock prices are the Earning Per Share variable. indicated by the significance value produced by the variable is smaller than the level of = 5%, while the PER, DER, ROA variables have no significant effect on stock prices. The test results show that the model used in the study is feasible and can be used for subsequent analysis. This result is also supported by the acquisition of a multiple correlation coefficient of 91.9% which indicates that the relationship between the independent variables together with the rise and fall of stock prices is strong. The result of testing the coefficient of determination (R Square) is indicated by a value of 84.4% meaning that the influence of the independent variable on the dependent variable is very large, while the remaining 15.6% is influenced by other models outside the regression model. The results of the partial determination coefficient test show that the Earning Per Share variable has the highest coefficient of determination. This indicates that these variables have a dominant influence on stock prices. Keywords : Earning Per Share, Price Earning Ratio, Debt to Equity Ratio, Return On Asset, Stock Price, Financial Performance